Equipment, Automation, Rock Mechanics Principles And Safety Interfaces In The Control Of Roof And Ribs Of Mines - James J. Scott (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
INTRODUCTION This paper presents the basic principles which must be followed to create a truly inherently safe mining system. The need to relate the support mechanism to be employed to the ground reaction curve and basic rock mechanics principles will be pointed out. The support system must function in concert with the deformations that are inherent in the selected mining system. Following the support selection, the mechanics for installing support must be developed. This is best done through a cooperative effort between mine engineers, mine operators, safety personnel, equipment sup- pliers, and government inspectors both state and federal. Accident statistics, near miss statistics, review of equipment used by others, geologic features, etc. will necessarily have to be studied. The goal of equipment development and selection should be to develop inherent safety by removing the miner from the hazard area or by providing absolute protection for the miner if he must work in close proximity to the potential fall of ground. The role of good productivity in reducing the numbers of men exposed to hazards is emphasized as a good safety measure ROCK MECHANICS PRINCIPLES A thorough understanding of the ground reaction curve surrounding openings to be created is essential in the